2020
DOI: 10.3390/healthcare8020142
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Nurses’ Perception of Death and Self-Reported Performance of End-of-Life Care: Mediating Role of Attitude towards End-of-Life Care

Abstract: Few studies have explored how nurses in acute care hospitals perceive and perform end-of-life care in Korea. Therefore, this study aimed to evaluate the influence of nurses’ perceptions of death on end-of-life care performance and analyze the mediating role of attitude towards end-of-life care among hospital nurses. This cross-sectional study included a total of 250 nurses who have had experience with end-of-life care from four general hospitals in Korea. We used the Korean validated tools with the View of Lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Some studies found the frequency of EOL care supportive behaviors was the factor affecting EOL care competency [37,38]. This is mainly because if a nurse has more EOL patient experience, the more positive their nursing attitude will be, and they are more willing to talk about EOL care problems and death [3,39]. Weigel and colleagues [40] proposed that this phenomenon occurs because nurses' various care skills, especially communication skills, develop as the number of patients increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found the frequency of EOL care supportive behaviors was the factor affecting EOL care competency [37,38]. This is mainly because if a nurse has more EOL patient experience, the more positive their nursing attitude will be, and they are more willing to talk about EOL care problems and death [3,39]. Weigel and colleagues [40] proposed that this phenomenon occurs because nurses' various care skills, especially communication skills, develop as the number of patients increases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that EOL care courses played an important role in affecting behavior toward EOL care. Offering these courses can help directly either by improving nurses' attitudes or enhancing direct patient care skills [39,46]. Systematic EOL care training generally includes death education, psychological and spiritual care, and communication skills [47].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses' recognition of, and response to, ‘sovereign expressions of life’ and ‘the ethical demand’ (Rushton & Edvardsson, 2018), manifested wherever misalignments occurred regarding the decisions taken during end‐of‐life care, and were a significant source of moral and emotional distress among nurses during end‐of‐life care and in the event of a death (Hinderer, 2012; McCourt et al, 2013; Park, Lee, et al, 2020; Park, Yun‐Mi, et al, 2020; Ranse et al, 2012; Zheng et al, 2018). Misalignments occurred most often when a person transitioned from curative to palliative care or from palliative to end‐of‐life care.…”
Section: Ethicsmentioning
confidence: 99%
“…Adequate preparation increased newer nurses' resilience by providing opportunities for them to express and work through their ‘fear of death’ or ‘death anxiety’. ‘On the job’ experience exposed new nurses to healthy coping behaviours modelled by more experienced nurses while at the same time, provided coaching opportunities that enabled them to become proficient in the relevant practical skills and assume the ‘correct’ comportment in the advent of a death (Croxon et al, 2018; Ek et al, 2014; Kisorio & Langley, 2016; McCourt et al, 2013; Park, Yun‐Mi, et al, 2020; Zomorodi & Lynn, 2010).…”
Section: Positionality: Situating Oneself In Relation To ‘The Good Death'mentioning
confidence: 99%
“…The perception of death is also formed as a result of individuals' personal experiences and develops depending on what they have seen concerning death, the age period they are in, and their religious and cultural values. Hence, everyone's perception of death is unique (3,4).…”
mentioning
confidence: 99%